Managing e-publishing: perfect harmony for serialists - Robertson, Wendy C.; Simser, Charlene N. (My University, 2013)
This paper describes two serialists who use skills honed in their respective serials departments to show how those skills adapt to the world of e-publishing. The presenters will discuss their roles in e-publishing and their respective university presses and library publishing programs. How have their libraries reorganized to provide resources for supporting these new roles? The daily work of an e-publishing librarian will be reviewed, including an overview of working with Digital Commons and Open Journal Systems (OJS), two e-press platforms. The presenters will also discuss funding and sustainability of the programs and working with open access and subscription titles.
Keywords: Digital Commons; Open Journal Systems; Open access; E-publishing; Library as publisher